2005
DOI: 10.2106/jbjs.d.01952
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Tendon-Bone Healing of Anterior Cruciate Ligament Grafts by Blockage of Matrix Metalloproteinases

Abstract: The present study demonstrated that alpha2-macroglobulin blockade of matrix metalloproteinases can enhance bone-tendon healing. This effect of alpha2-macroglobulin could occur through its effect solely on collagenase or on a subset of matrix metalloproteinases that are present at the healing interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 30 publications
2
52
2
Order By: Relevance
“…Studies have shown that A2M inhibits activities of ADAMTS-4,-5,-7, -12 (20, 21), MMP-13 activity (34) Thus, the protease/A2M balance may play an important role in mediating cartilage destruction by catabolic factors. We found that the concentrations of MMP-13 were 2.8-fold higher in human OA SF samples when compared with serum, but A2M levels were 7-fold lower in human OA SF samples than in serum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that A2M inhibits activities of ADAMTS-4,-5,-7, -12 (20, 21), MMP-13 activity (34) Thus, the protease/A2M balance may play an important role in mediating cartilage destruction by catabolic factors. We found that the concentrations of MMP-13 were 2.8-fold higher in human OA SF samples when compared with serum, but A2M levels were 7-fold lower in human OA SF samples than in serum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…35,37,40,41,44,45,50 Synovial fluid has been shown to contain various matrix metalloproteinases that can impede tendonebone healing. 9,15,18,29 These cytokines and matrix metalloproteinases are elevated in the setting of rotator cuff tears. 49 In addition, the subacromial bursa in patients with rotator cuff tears contains a high level of expression of proinflammatory cytokines, proteinases, and cyclooxygenase enzymes, which are known to produce a catabolic environment.…”
Section: Discussionmentioning
confidence: 99%
“…42 Access of synovial fluid to the zone of healing has been studied in the anterior cruciate reconstruction model. 3,9,18 When the aperture site is closed off from the synovial fluid at the site of fixation, the intratunnel remodeling and healing is improved. 18 In addition, Demirag et al 9 demonstrated that blockade of matrix metalloproteinases can enhance boneetendon healing after anterior cruciate recontruction.…”
Section: Discussionmentioning
confidence: 99%
“…6 On the other hand, rabbit models of anterior cruciate ligament reconstruction have showed that the endogenous MMP inhibitor A2M, injected intra-articularly, improves strength and histologic features of tendon-to-bone healing. 34 A transient reduction of the strength of the suture construct in tendons occurs in the immediate postoperative period after surgical repair of tendon rupture. 116,120 Postoperatively, MMPs may mediate the degradative process that occurs in the direct vicinity of the sutures, leading to weakening of tendon tissue around the suture.…”
Section: Mmp In Tendon Healingmentioning
confidence: 99%